Haematological parameters of apparently healthy neonates at the Federal Medical Centre Bida, North Central Nigeria - Ojewole OE; Abubakar U; Olowu AO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Haematological parameters are used as screening tools for patient's care and treatment. Objective: To determine the haematological parameters of apparently healthy term Nigerian babies and generate normative data. Methods: This was a descriptive, longitudinal study of consecutively recruited babies. The haematological parameters were determined using venous blood samples drawn at delivery and on the 14th day of life using a haematology auto-analyser. Results: Of the 309 babies recruited on the first day of life, 160 (51.8%) were males while 149 (48.2%) were females. Two hundred and seventy-nine (90.3%) were delivered vaginally. Most (75%) of the neonates were of Nupe origin. The mean haematocrit, haemoglobin concentration, Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH), Mean Corpuscular Haemoglobin Concentration (MCHC), Red Blood Cell and reticulocyte count on Day 1 were 48.8±8.0%, 15.0±2.6g/dl, 104.1±8.8fl, 31.9±3.3pg, 30.7±1.7g/dl, 4.7±0.9 (×109/l) and 2.0±1.4% respectively. Corresponding Day 14 values were 41.2±5.2%, 12.8±1.9g/dl, 97.2±9.8fl, 30.3±3.8pg, 31.1±1.7g/dl, 4.5±0.6 (×109/l) and 1.0±0.7% respectively. The mean White Blood Cell (WBC) and platelet counts were 13.3±4.8 (×109/l) and 228.3±81.2 (×109/l) respectively, on the 1st day of life and 10.1±2.4 (×109/l) and 370.1±120.7 (×109/l) respectively on the 14th day. The mean differential WBC counts were 49.4±12.0% for neutrophils and 37.4±11.3% for lymphocytes on the 1st day and 32.4±10.0% and 52.8±9.3% respectively on the 14th day. Conclusion: Neonates from Bida have haematological parameters comparable with previously reported values from other parts of Nigeria.